INFORMATION GAP TECHNIQUE BASED ON STUDENTS’ WILLINGNESS TO COMMUNICATE IN SPEAKING ACHIEVEMENT TEKNIK KESENJANGAN INFORMASI BERDASARKAN KESIAPAN SISWA BERKOMUNIKASI DALAM PENINGKATAN PRESTASI BERBICARA - Burhanuddin, Wildhan; Yassi, Abdul Hakim; Jubhari, Ria Rosdiana (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2015)
Willingness to communicate (WTC) has important roles in students’ learning. It refers to the personal variable which can affect students’ learning process and at the last stage affect students’ speaking achievement. The purpose of the research was to find out the willingness to communicate as a students’ personality through students’ response in scoring system of designed questionnaire and effectiveness of information gap technique as a teaching method to improve students’ speaking achievement. The population of this research was 368 students from 10 classes at the second semester, English Department, at the Muhammadiyah University of Makassar. This research was quasi-experimental. The sample was taken by purposive sampling. The total sample was 24 for the experimental group and 19 for the control group. Data collected from two groups of students, experimental and the control group that had been analyzed by three raters and tabulated in the table of students’ score was tabulated in Excel 2007 (Windows program and analyzed in IBM statistical package and service solution (SPPSS 20). The findings showed that there was a significant difference between pretest and post test of the experimental group while the control group that was not the significant difference between pretest and posttest. It proved that Information gap technique based on WTC improved the students’ speaking achievement.